Trends in the use and nonmedical use of sedatives-hypnotics in the population aged 12 to 64 years in Taiwan: a comparative analysis of the national surveys in 2014 and 2018 - Wei-Yi Tsay; Lian-Yu Chen; Shang-Chi Wu; Po-Chang Hsiao; Te-Tien Ting; Cheng-Fang Yen; Shu-Sen Chang; Chung-Yi Li; Hao-Jan Yang; Chia-Feng Yen; Chuan-Yu Chen; Jiun-Hau Huang; et al. (BMC, 2024)
Abstract Background Many countries, including Taiwan, have tightened regulations on prescribing sedatives-hypnotics over the concern of their associated adverse health effects. However, it remains seldom investigated whether different age-sex strata have differential trends in national surveys over time for either the use or nonmedical use (NMU) of sedatives-hypnotics. Comparing Taiwan's two national surveys in 2014 and 2018, we aimed to examine (1) the population's trends for the prevalence of past-year use and NMU of sedatives-hypnotics overall and in age-sex strata; (2) trends for sociodemographic subgroups for those age-sex strata with significant changes in past-year use and NMU of sedatives-hypnotics over time; and (3) trends for sources of and motives for NMU of sedatives-hypnotics. Methods The national survey enrolled 17,837 participants in 2014 (response rate = 62.2%) and 18,626 participants in 2018 (response rate = 64.6%) of citizens aged 12-64 years. Each participant anonymously completed a computer-assisted self-interview. The questionnaire consisted of sociodemographic variables and the use of various psychoactive substances and sedative-hypnotics, among others. NMU of sedative-hypnotics was defined as using the drug without a prescription, or more frequently, or in larger doses than prescribed. To compare the prevalence between the two waves, we conducted multivariable logistic regression analysis and the difference-in-differences in prevalence was examined with an interaction term between survey year and sex. Results We found decreasing trends in young adult (18-39 years old) males for both past-year use (3.07-2.29%) and NMU (0.84-0.18%), but increasing trends in adolescents (0.42-0.80%) and young adult females (2.91-3.81%) for past-year use and in adolescents (0.16-0.39%) and middle-aged adult (40-64 years old) females (0.73-1.14%) for past-year NMU of sedatives-hypnotics. Among the young and middle-aged adult females, the increasing trends for past-year use and NMU, respectively, were found to occur mainly in certain sociodemographic subgroups, with alcohol users being the overlapping subgroup. Conclusions The differential trends over time of past-year use or NMU of sedatives-hypnotics in different age-sex strata in the population have policy implications to curtail the increasing trend over time.